Technologies, strategies, and cautions when deconvoluting genome‐wide association signals: FTO in focus. (7th March 2023) - Pahl, Matthew C.; Grant, Struan F. A.; Leibel, Rudolph L.; Stratigopoulos, George
Summary: Genome‐wide association studies have revealed a plethora of genetic variants that correlate with polygenic conditions. However, causal molecular mechanisms have proven challenging to fully define. Without such information, the associations are not physiologically useful or clinically actionable. By reviewing studies of the FTO locus in the genetic etiology of obesity, we wish to highlight advances in the field fueled by the evolution of technical and analytic strategies in assessing the molecular bases for genetic associations. Particular attention is drawn to extrapolating experimental findings from animal models and cell types to humans, as well as technical aspects used to identify long‐range DNA interactions and their biological relevance with regard to the associated trait. A unifying model is proposed by which independent obesogenic pathways regulated by multiple FTO variants and genes are integrated at the primary cilium, a cellular antenna where signaling molecules that control energy balance convene.